Gradient gradient wave-absorbing PMI foam material as well as preparation method and application thereof
The PMI foam material with gradient design solves the dispersion and compatibility problems of the absorber, achieving broadband and efficient absorbing performance, which is suitable for radar antenna covers and aerospace.
Patent Information
- Application Number
- CN202511093671.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-09-26
AI Technical Summary
Existing absorbing PMI foam materials have problems with the dispersion and uniformity of the absorber, and the absorber has poor compatibility with the PMI raw material, resulting in unstable and uneven absorbing performance, a narrow absorbing band, and low absorption efficiency, which makes it difficult to meet the needs of high-performance, wide-band stealth materials.
A gradient design is adopted, and PMI foam beads are impregnated in an adhesive containing an absorber. A gradient absorbing PMI foam material is formed through high-temperature foaming. The surface low dielectric constant layer matches the air impedance, the middle transition layer enhances the penetration of electromagnetic waves, and the bottom high loss layer deeply loses electromagnetic waves, realizing layer-by-layer impedance matching and stepped loss absorption of electromagnetic waves.
It significantly broadens the absorption band, improves the absorption intensity, ensures the uniformity and stability of the absorbing performance, breaks through the performance limitations of a single type of absorber, and achieves a broadband and efficient absorbing effect.
Smart Images

Figure BDA0005534745000000101 
Figure BDA0005534745000000111 
Figure BDA0005534745000000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of PMI foam material preparation, and in particular to a gradient-varying wave-absorbing PMI foam material, a preparation method and use thereof. Background Art
[0002] The conventional preparation process for absorbing polymethacrylimide (PMI) foam is to directly add an absorber (primarily a carbon-based material) to the PMI raw material for bulk polymerization to produce a precursor sheet, which is then foamed at high temperature and post-processed to obtain the finished product. This method has the following key issues:
[0003] Absorber dispersion and uniformity issues: During the polymerization process, the added absorber tends to settle or agglomerate, resulting in uneven distribution of the absorber within the foam sheet and at different locations. This not only affects the consistency of the foam's mechanical properties but, more critically, leads to unstable and uneven absorption performance in three dimensions.
[0004] Absorber-raw material compatibility issue: The methacrylic acid contained in the PMI foam raw material easily reacts with the magnetic absorber, interfering with the normal gasification and expansion of the foaming agent and the formation of the pore structure, thereby damaging the core physical properties of the foam.
[0005] Performance bottlenecks of carbon-based absorbers: Mainstream carbon-based absorbers have inherent defects: (a) poor impedance matching, narrow absorption band, and low absorption efficiency when used alone; (b) their huge specific surface area and high surface energy make it difficult to disperse evenly and stably exist in the resin system (PMI raw material), greatly limiting the upper limit of their additive amount.
[0006] Insufficient overall performance: The above problems jointly lead to the core defects of existing absorbing PMI foam, such as narrow absorption band, low absorption efficiency, and uneven spatial distribution of performance, which makes it difficult to meet the application requirements of high-performance, wide-band stealth materials. Summary of the Invention
[0007] Based on the technical problems existing in the prior art, the present application provides a gradient-graded absorbing PMI foam material, a preparation method and its use. The gradient-graded absorbing material prepared by the method described in the present application matches the air impedance through the surface low dielectric constant layer to reduce incident reflection; the middle transition layer enhances electromagnetic wave penetration; the bottom high-loss layer deeply loses electromagnetic waves. The gradient dielectric change significantly broadens the absorption band. The continuous gradient design eliminates the impedance step and air gap between layers of the traditional multi-layer structure, avoiding interlayer separation and reflection loss.
[0008] The specific technical solutions of this application are as follows:
[0009] 1. A method for preparing a gradient-varying absorbing PMI foam material, comprising:
[0010] The PMI foam beads were immersed in an adhesive containing an absorbent, and then dried to obtain absorbent functionalized beads containing different loads of absorbent.
[0011] The wave-absorbing functionalized beads containing different loads of the wave-absorbing agent are sequentially laid on the surface of the mold and foamed at high temperature to obtain a gradient-varying wave-absorbing PMI foam material;
[0012] In the direction away from the mold surface, the loading amount of the wave absorbing agent in the wave absorbing functionalized beads increases successively.
[0013] 2. The method according to claim 1, wherein the mold is three-layer, wherein
[0014] The first layer of the absorbing functionalized beads has an absorber loading of 5-15%.
[0015] The second layer of absorbent functionalized beads has a loading amount of 10-30%;
[0016] The loading amount of the absorber in the third layer of the absorbent functionalized beads is 20-80%.
[0017] 3. The method according to item 1 or 2, wherein the absorber is selected from one or more of conductive carbon black, graphite, carbon fiber, carbon nanotubes, graphene, silicon carbide, barium titanate, silicon nitride, iron nitride, ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof, and alloy fibers of iron, nickel and cobalt.
[0018] 4. The method according to any one of items 1 to 3, wherein the adhesive contains an absorber, a solvent and a polymer. Optionally, based on the mass percentage in the adhesive, the absorber is 5-25%, the solvent is 20-80%, and the polymer is 15-50%.
[0019] 5. The method according to item 4, wherein the high molecular polymer is selected from one or more of polyamide, polyimide, epoxy resin, polymethacrylimide, polymethyl methacrylate, (meth) acrylonitrile (meth) acrylic acid copolymer, polybenzimidazole and polypyromellitimide; and / or
[0020] The solvent is selected from one or more of acetone, toluene, xylene, ethyl acetate, ethanol, isopropanol and methyl ethyl ketone.
[0021] 6. The method according to any one of items 1 to 5, wherein the particle size of the PMI foam beads is 1 to 5 mm;
[0022] Optionally, the drying temperature is 40-120°C.
[0023] 7. The method according to any one of items 1 to 6, wherein the foaming temperature is 150-270° C.;
[0024] Optionally, the foaming time is 1.5-4 hours.
[0025] 8. A gradient-varying wave-absorbing PMI foam material, prepared by the method described in any one of items 1 to 7.
[0026] 9. Use of the gradient-varying absorbing PMI foam material described in item 8 in radar antenna covers or aerospace.
[0027] Effects of the Invention
[0028] The method described in this application utilizes a gradient structure to precisely control the spatial distribution of electromagnetic parameters (dielectric / magnetic loss), thereby achieving layer-by-layer impedance matching and a stepped loss absorption mechanism for electromagnetic waves, fundamentally overcoming the bottlenecks of narrow absorption bandwidth and low efficiency, significantly broadening the effective absorption bandwidth, and improving the absorption intensity.
[0029] In addition, by introducing absorbers of different types and concentrations in layers, the problems of sedimentation, agglomeration and poor compatibility (such as the reactivity of magnetic absorbers) caused by adding a large amount of absorbers at one time are avoided, ensuring the uniformity, consistency and stability of the absorbing performance and pore structure within the material.
[0030] In addition, the gradient design releases the selective composite potential of the absorber (such as using carbon, magnetic materials or a combination in different layers), breaking through the performance limitations and additive restrictions of a single type of absorber (such as pure carbon), and achieving a synergistic absorption effect of 1+1>2 and higher design freedom. DETAILED DESCRIPTION
[0031] The present application is described in detail below in conjunction with the described embodiments. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0032] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of this application shall be as defined by the attached claims.
[0033] The present application provides a method for preparing a gradient-varying wave-absorbing PMI foam material, which comprises:
[0034] The PMI foam beads were immersed in an adhesive containing an absorbent, and then dried to obtain absorbent functionalized beads containing different loads of absorbent.
[0035] The wave-absorbing functionalized beads containing different loads of the wave-absorbing agent are sequentially laid on the surface of the mold and foamed at high temperature to obtain a gradient-varying wave-absorbing PMI foam material;
[0036] In the direction away from the mold surface, the loading amount of the wave absorbing agent in the wave absorbing functionalized beads increases successively.
[0037] In the present application, the PMI foam beads may be PMI foam beads conventionally used in the art, or may be prepared by conventional methods in the art, for example, by the following method:
[0038] The raw materials are prepolymerized in the first stage to obtain prepolymerized materials.
[0039] When the viscosity of the prepolymer material reaches 20-200 Pa·s, it is extruded and shaped to obtain prepolymer particles of specific shape and size.
[0040] The prepolymerized particles are subjected to a second stage of prepolymerization,
[0041] The particles after the second stage pre-polymerization are further subjected to high-temperature pre-foaming treatment to obtain the foamable polymer foam particles with customized shapes.
[0042] Optionally, the raw materials include monomers, initiators, cross-linking agents, foaming agents and other auxiliary agents.
[0043] Optionally, the monomers include one or more of acrylic acid, methacrylic acid, acrylonitrile, methacrylonitrile, methyl methacrylate, amide compounds, acid anhydride compounds or styrene, preferably acrylic acid / methacrylic acid, and acrylonitrile / methacrylonitrile.
[0044] Optionally, the other auxiliary agents include one or more of flame retardants, retarders, nucleating agents, dispersants, release agents, heat-resistant agents, and antioxidants.
[0045] Optionally, the initiator is selected from one or more of tert-amyl peroxyacetate, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxybenzoate, tert-butyl peroxybenzoate, azobisisobutyronitrile and azoisobutylcyanamide; and the foaming agent is selected from one or more of ethanol, propanol, isopropanol, water, tert-butanol and amyl alcohol.
[0046] Optionally, the mass fractions of the components in the raw materials are: 80-150 parts of monomer, 0.04 to 10 parts of initiator, 0.02 to 5 parts of cross-linking agent, 0.5 to 25 parts of foaming agent, and 0.9 to 20 parts of other auxiliary agents.
[0047] Optionally, the raw materials are mixed and firstly prepolymerized to obtain a prepolymerized material. The reaction temperature of the first prepolymerization is 30-60° C. and the reaction time is 10-20 hours.
[0048] Optionally, after the first stage of prepolymerization, when the prepolymerized material has a viscosity of 20-200 Pa·s, it is extruded and further shaped into a specific shape.
[0049] Optionally, the temperature of the second stage prepolymerization is 40-80° C., and the reaction time is 10-20 hours.
[0050] Optionally, after the second stage prepolymerization of the prepolymerized particles is completed, the prepolymerized particles are further subjected to a high temperature pre-foaming treatment to obtain the expandable polymer foam particles of the customized shape.
[0051] Optionally, the reaction temperature of the high-temperature pre-foaming treatment is 170-220° C., and the reaction time is 15-90 minutes.
[0052] In the method described herein, the absorber in the adhesive is impregnated to form a surface coating. During the high-temperature foaming process, the surface coating expands with the beads, anchoring the absorber at the cell wall interfaces of the PMI foam framework, forming a three-dimensional dispersed network. This structure effectively inhibits absorber migration or aggregation, ensuring multiple reflections and absorption of electromagnetic waves within the foam, significantly improving frequency coverage and reflection attenuation stability. Furthermore, the PMI foam beads are impregnated with an absorber-containing adhesive, which melts and penetrates the micropores on the bead surface during the high-temperature molding stage. After curing, a dual bond of chemical crosslinking and mechanical interlocking is formed. The interfacial shear strength can reach over 80% of that of the original PMI foam, preventing interface weakening caused by absorber doping.
[0053] In the present application, there is no limitation on the time for immersing the PMI foam beads in the adhesive containing the absorbent. A person skilled in the art can select a desired immersion time based on the required loading amount of the absorbent. For example, the immersion time can be 0.1-1 h, for example, 0.1 h, 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, or 1 h.
[0054] In this application, there is no limitation on the method for determining the loading amount. A person skilled in the art may use conventional methods in the art to determine the loading amount. For example, the following method may be used for determination: the weight of the particles before immersion is recorded as m1, the weight of the particles after immersion and drying is recorded as m2, and the loading amount = (m2-m1) / m1, thereby obtaining the loading amount of the absorber.
[0055] In some embodiments, the mold is three-layered, wherein
[0056] The first layer of the absorbing functionalized beads has an absorber loading of 5-15%.
[0057] The second layer of absorbent functionalized beads has a loading amount of 10-30%;
[0058] The third layer of absorbing functionalized beads has an absorber loading of 20-80%. In some embodiments, the absorber is selected from one or more of conductive carbon black, graphite, carbon fiber, carbon nanotubes, graphene, silicon carbide, barium titanate, silicon nitride, iron nitride, ferrite, carbonyl iron powder, iron, cobalt, nickel, and alloy powders thereof, and iron, nickel, and cobalt alloy fibers.
[0059] In the present application, the loading amount of the absorber in the absorbing functionalized beads increases successively in the mold, that is, the loading amount of the absorber increases successively from the first layer to the third layer.
[0060] In the present application, there is no limitation on the absorber used in each layer. The above-mentioned absorbers can be used in each layer, preferably comprising any one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride, or a mixture of one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride with one or more of ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof. Preferably, the absorber of the first layer and the absorber of the second layer can independently comprise one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride; the absorber of the third layer can comprise a mixture of one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride with any one or more of ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof. In the present application, there is no restriction on the ratio of one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride to one or more of ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof. Those skilled in the art can select the ratio of the two based on actual needs. For example, the ratio of the two can be 10-20:40-70. For example, the ratio of one or more of conductive carbon black, graphene, carbon nanotubes and silicon nitride to ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof can be 10-20:40-70. , iron, cobalt, nickel and their alloy powders, the ratio of one or more of them can be 10:40, 10:45, 10:50, 10:55, 10:60, 10:65, 10:70, 11:40, 11:45, 11:50, 11:55, 11:60, 11:65, 11:70, 12:40, 12:45, 12:50, 12:55, 12:60, 12:65, 12:70, 13:40, 13:45 , 13:50, 13:55, 13:60, 13:65, 13:70, 14:40, 14:45, 14:50, 14:55, 14:60, 14:65, 14:70, 15:40, 15:45, 15:50, 15:55, 15:60, 15:65, 15:70, 16:40, 16:45, 16:50, 16:55, 16:60, 16:65, 16:70, 17:40, 17:45, 17:50, 17:55, 17:60, 17:65, 17:70, 18:40, 18:45, 18:50, 18:55, 18:60, 18:65, 18:70, 19:40, 19:45, 19:50, 19:55, 19:60, 19:65, 19:70, 20:40, 20:45, 20:50, 20:55, 20:60, 20:65, 20:70, etc.
[0061] For example, the loading amount of the absorber in the first layer of absorbing functionalized beads can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0062] The loading amount of the absorber in the second layer of the absorbing functionalized beads can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc.
[0063] The loading amount of the absorber in the third layer of the absorbing functionalized beads can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.
[0064] In some embodiments, the adhesive contains an absorber, a solvent, and a polymer. In the present application, there is no limitation on the mass percentages of the absorber, solvent, and polymer in the adhesive. Those skilled in the art can make routine selections based on actual needs, as long as the conditions of the present application are met. For example, in terms of mass percentage in the adhesive, the absorber is 5-25%, the solvent is 20-80%, and the polymer is 15-50%.
[0065] For example, the absorber can be 5%, 10%, 15%, 20%, 25%, etc.; the solvent can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.; the high molecular polymer can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.
[0066] In the present application, there is no restriction on the preparation method of the adhesive. The adhesive can be obtained by mixing the absorber, solvent and polymer by conventional methods in the art. Preferably, the absorber, solvent and polymer are mixed by stirring to obtain the adhesive. Preferably, the stirring time is 0.5-1h and the stirring speed can be 1000-2000rpm.
[0067] For example, the stirring time can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, or 1 h.
[0068] The stirring speed may be 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, 1700 rpm, 1800 rpm, 1900 rpm, 2000 rpm, etc.
[0069] In some embodiments, the high molecular polymer is selected from one or more of polyamide, polyimide, epoxy resin, polymethacrylimide, polymethyl methacrylate, (meth)acrylonitrile (meth)acrylic acid copolymer, polybenzimidazole and polypyromellitimide; and / or
[0070] The solvent is selected from one or more of acetone, toluene, xylene, ethyl acetate, ethanol, isopropanol and methyl ethyl ketone.
[0071] In some embodiments, the particle size of the PMI foam beads is 1-5 mm;
[0072] Optionally, the drying temperature is 40-120°C.
[0073] For example, the particle size of the PMI foam beads may be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, or 5 mm.
[0074] In the present application, the particle size can be determined by conventional methods in the art.
[0075] The present application uses PMI foam beads of such a particle size to enable a higher loading amount of the absorber.
[0076] The drying temperature may be, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, or 120°C.
[0077] In some embodiments, the foaming temperature is 150-270°C;
[0078] Optionally, the foaming time is 1.5-4 hours.
[0079] For example, the foaming temperature is 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, etc.
[0080] The foaming time can be 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc.
[0081] The method described in this application utilizes a gradient structure to precisely control the spatial distribution of electromagnetic parameters (dielectric / magnetic loss), thereby achieving layer-by-layer impedance matching and a stepped loss absorption mechanism for electromagnetic waves, fundamentally overcoming the bottlenecks of narrow absorption bandwidth and low efficiency, significantly broadening the effective absorption bandwidth, and improving the absorption intensity.
[0082] The method described in this application introduces absorbers of different types and concentrations in layers, avoiding the problems of sedimentation, agglomeration, and poor compatibility (such as the reactivity of magnetic absorbers) caused by the composite addition of a large amount of absorbers at one time, thereby ensuring the uniformity, consistency, and stability of the absorbing performance and pore structure within the material.
[0083] The method described in this application uses a gradient design to release the selective composite potential of the absorber (such as using carbon-based materials, magnetic materials or a combination in different layers), breaking through the performance limitations and additive restrictions of a single type of absorber (such as pure carbon-based materials), and achieving a synergistic absorption effect of 1+1>2 and a higher degree of design freedom.
[0084] The method described in this application overcomes the negative effects of absorber doping on the foaming structure and mechanical properties through surface functionalization coating and interface welding reinforcement. Through the "gradually varying impedance matching-deep loss" synergistic mechanism, it breaks through the bottleneck of "narrow band, high reflection, and interlayer weakening" of traditional absorbing materials, and achieves multi-objective optimization of "strong, wide, stable, and light" absorbing PMI foam.
[0085] The present application provides a gradient-varying wave-absorbing PMI foam material, which is prepared by any of the methods described above.
[0086] The gradient-varying wave-absorbing PMI foam material described in the present application has the characteristics of broadband high-efficiency absorption and lightweight.
[0087] The present application provides the use of the above-mentioned gradient-varying absorbing PMI foam material in radar antenna covers or aerospace.
[0088] In the gradient-varying absorbing PMI foam material described in this application, the surface low dielectric constant layer matches the air impedance to reduce incident reflection; the middle transition layer enhances electromagnetic wave penetration; the bottom high-loss layer deeply loses electromagnetic waves. The gradient dielectric change significantly broadens the absorption band. This continuous gradient design eliminates the impedance steps and air gaps between layers of the traditional multi-layer structure, avoids interlayer separation and reflection loss, and can thus be used in radar antenna covers or aerospace.
[0089] Example
[0090] This application provides general and / or specific descriptions of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., percentage by weight. Reagents or instruments used without manufacturer indication are commercially available conventional reagents. The expandable PMI foam beads were prepared as follows:
[0091] (1) The raw materials were subjected to a first-stage prepolymerization at 55°C for 15 hours to obtain a prepolymer. The raw material composition (by mass) was: 80 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.5 parts of azobisisobutyronitrile (initiator), 2 parts of acrylamide (crosslinking agent), 8 parts of isopropyl alcohol (foaming agent), and 3 parts of nano-silica (nucleating agent).
[0092] (2) The prepolymer having a viscosity of 110 Pa·s was extruded into a long thin plate, and shaped by a roller having spherical processing grooves to obtain spherical prepolymer particles with an average particle size of 1.8 mm.
[0093] (3) The spherical prepolymerized particles obtained in the previous step were further subjected to the second stage of prepolymerization in an oven at 40-80°C for 15 hours.
[0094] (4) The product was then treated at a high temperature of 195°C for 1 hour to obtain expandable polymer foam particles with a particle size of 5 mm.
[0095] (5) The expandable polymer foam particles obtained in the previous step are filled into a special-shaped mold as conventionally used in the art, preheated from room temperature to 160°C for 1 hour, and then foamed and cured at 230°C for 6 hours. The particles expand and foam, fill the mold cavity, and are completely cured.
[0096] (6) After foaming, the mold is cooled and the foamed core is removed to obtain expandable PMI foam beads with a particle size of 2.8 mm.
[0097] Example 1
[0098] A polymer matrix (25g polymethyl methacrylate), an organic solvent (60g acetone) and 5g of different absorbers were added to a reactor respectively, and dispersed by high-speed shear to form a uniformly dispersed absorbing adhesive system. Subsequently, 80g of expandable PMI foam beads (particle size 2.8mm) were impregnated in the adhesive. The absorber load was adjusted by controlling the immersion time. After drying, absorbing functionalized beads with different electromagnetic parameters were obtained. The mold was divided into three layers. According to the electromagnetic parameter design, absorbing functionalized beads with a load of 5wt% of the absorber were paved on the first layer of the mold, absorbing functionalized beads with a load of 10wt% of the absorber were paved on the second layer of the mold, and absorbing functionalized beads with a load of 10wt% of the absorber were paved on the third layer of the mold. The absorber loading amount was 45 wt% of absorbing functionalized beads. The absorbers for the first and second layers were carbon nanotubes, and the absorbers for the third layer were hydroxyl iron powder and carbon nanotubes (the mass ratio of hydroxyl iron powder to carbon nanotubes was 8:2). The absorbing functionalized beads were subjected to a high-temperature foaming treatment to form a gradient-graded PMI foam with broadband absorption characteristics. The high-temperature foaming temperature was 180°C and the high-temperature foaming time was 2.8 hours. The absorption test method was as follows: the obtained PMI foam was formed into a 300*300*30 sheet and tested using GJB2038A-2011 to obtain a curve. The peak value in the curve was taken as the experimental data of the absorption effect. The results are shown in Table 1.
[0099] Example 2-16
[0100] The difference between Examples 2-17 and Example 1 is that the gradient PMI foam obtained by using different absorbers or different absorber loading amounts in each layer was tested in the same manner as in Example 1, and the results are shown in Table 1.
[0101] Comparative Example 1
[0102] Comparative Example 1 is compared with Example 1. The loading amount of each layer of the absorber is 5% to obtain PMI foam. The test is carried out in the same manner as in Example 1. The results are shown in Table 1.
[0103] Comparative Example 2
[0104] Comparative Example 2 is compared with Example 1, except that the loading amount of the first layer of carbon nanotubes is 45%, the loading amount of the second layer of carbon nanotubes is 10%, and the loading amount of the third layer of carbonyl iron powder and carbon nanotubes is 5%. The test was carried out in the same manner as in Example 1, and the results are shown in Table 1.
[0105] Comparative Example 3
[0106] Compared with Example 1, Comparative Example 3 is to directly spread the absorber of Example 1 on the surface of the mold to obtain PMI foam. The obtained PMI foam has uneven absorbing effect, that is, the local absorbing effect is uneven.
[0107] Table 1
[0108]
[0109]
[0110]
[0111] It can be seen from the above table that the PMI foam prepared in this application has excellent wave absorbing performance, which can meet the corresponding wave absorbing performance standards.
[0112] The above description is merely a preferred embodiment of the present application and is not intended to limit the present application in any other manner. Any person skilled in the art may utilize the above disclosed technical content to modify or modify the present application into equivalent embodiments with equivalent variations. However, any simple modifications, equivalent variations, and modifications to the above embodiments that do not depart from the technical content of the present application and are based on the technical essence of the present application shall still fall within the scope of protection of the present application.
Claims
1. A method for preparing a gradient-varying absorbing PMI foam material, comprising: The PMI foam beads were immersed in an adhesive containing an absorbent, and then dried to obtain absorbent functionalized beads containing different loads of absorbent. The wave-absorbing functionalized beads containing different loads of the wave-absorbing agent are sequentially laid on the surface of the mold and foamed at high temperature to obtain a gradient-varying wave-absorbing PMI foam material; In the direction away from the mold surface, the loading amount of the wave absorbing agent in the wave absorbing functionalized beads increases successively.
2. The method according to claim 1, wherein the mold is three-layer, wherein The first layer of the absorbing functionalized beads has an absorber loading of 5-15%. The second layer of absorbent functionalized beads has a loading amount of 10-30%; The loading amount of the absorber in the third layer of the absorbent functionalized beads is 20-80%.
3. The method according to claim 1 or 2, wherein the absorber is one or more selected from the group consisting of conductive carbon black, graphite, carbon fiber, carbon nanotubes, graphene, silicon carbide, barium titanate, silicon nitride, iron nitride, ferrite, carbonyl iron powder, iron, cobalt, nickel and alloy powders thereof, and alloy fibers of iron, nickel and cobalt.
4. The method according to any one of claims 1 to 3, wherein the adhesive contains an absorber, a solvent, and a high molecular weight polymer. Optionally, based on the mass percentage of the adhesive, the absorber is 5-25%, the solvent is 20-80%, and the high molecular weight polymer is 15-50%.
5. The method according to claim 4, wherein the high molecular polymer is selected from one or more of polyamide, polyimide, epoxy resin, polymethacrylimide, polymethyl methacrylate, (meth)acrylonitrile (meth)acrylic acid copolymer, polybenzimidazole and polypyromellitimide; and / or The solvent is selected from one or more of acetone, toluene, xylene, ethyl acetate, ethanol, isopropanol and methyl ethyl ketone.
6. The method according to any one of claims 1 to 5, wherein the particle size of the PMI foam beads is 1 to 5 mm; Optionally, the drying temperature is 40-120°C.
7. The method according to any one of claims 1 to 6, wherein the foaming temperature is 150-270°C; Optionally, the foaming time is 1.5-4 hours.
8. A gradient-varying wave-absorbing PMI foam material, prepared by the method according to any one of claims 1 to 7.
9. Use of the gradient-varying wave-absorbing PMI foam material according to claim 8 in radar antenna covers or aerospace.
Citation Information
Cited By
Graphene / nickel-cobalt bimetallic oxide / PMI foam composite wave-absorbing material and preparation method and repairing method thereof
CN121628571A